2011
DOI: 10.1016/j.rcim.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Factory Templates for Digital Factories Framework

Abstract: The global industry is currently facing a growing increase in the competitiveness that forces companies to adopt and develop new strategies and methods of production. Therefore, one of the most relevant challenges in manufacturing engineering is innovatively integrating Product, Process and Factory dimensions and life cycles, in a holistic approach, from design to recycling/disposal and reuse. The challenge faced here is the synchronization and simultaneous generation of all three-domain models by integrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…In terms of manufacturing systems, it is becoming progressively clearer that the future generation of factories needs to be modular, scalable, flexible, open, agile and knowledge-based to allow for real-time adaption to continuously changing market trends and demands, technology options and regulations. In addition, this future generation of factories should be able to integrate each model and strategies capable of adapting their production system to the market's needs, of accelerating system design and of optimizing production [15].…”
Section: Factory Automation and Manufacturing Systemmentioning
confidence: 99%
“…In terms of manufacturing systems, it is becoming progressively clearer that the future generation of factories needs to be modular, scalable, flexible, open, agile and knowledge-based to allow for real-time adaption to continuously changing market trends and demands, technology options and regulations. In addition, this future generation of factories should be able to integrate each model and strategies capable of adapting their production system to the market's needs, of accelerating system design and of optimizing production [15].…”
Section: Factory Automation and Manufacturing Systemmentioning
confidence: 99%
“…Moreover, different researchers [14][15] state the need to build models or frameworks of international manufacturing systems that help managers to design and manage their networks, which should take into account the requirements for the next generation of factories such as agility, flexibility, modularity, adaptability, etc. [16]. Hence, the examination of the literature revealed that there is a lack of methods and techniques to accomplish the design and configuration process of a global production and logistic network.…”
Section: Research Gapmentioning
confidence: 99%
“…The framework intends to fill the gap left by the other ones which are really useful in a stable environment but they are not suitable in a market dynamic environment [28] where new facilities implementation [13,16,29] supplier network development [10,30,31] and multi-site network [14,32] are needed.…”
Section: Globope Frameworkmentioning
confidence: 99%
“…This approach is based on the leading and lagging factors that can influence the system's behavior. In order to fulfill these requirements, the so-called Performance Value Estimator (PVE) tool was used as a predictive control to monitor, learn and imitate the behavior of complex nonlinear systems that do not require profound knowledge of mathematics [19]. This tool, however, does require a thorough knowledge of the system that it will monitor and emulate.…”
Section: Fit Degree Supporting Toolsmentioning
confidence: 99%
“…In a higher mathematical layer of abstraction, the Kalman Filter can be seen as a tool that is used to estimate the instantaneous "state" of a dynamic system perturbed by white noise (random factors). Consequently, by incorporating these two significant approaches it was possible to develop a tool that is able to predict the evolution of the behavior of complex systems, minimizing the different errors and noises that can disturb the normal assessment of the performance of the system as presented by Azevedo and Almeida [19].…”
Section: Fit Degree Supporting Toolsmentioning
confidence: 99%